Melatonin alleviates endoplasmic reticulum stress and follicular granulosa cell apoptosis by regulating ATF4 to activate mTOR signaling pathway in chickens - Er-ying Hao; Xue-lu Liu; Xiang-yu Chen; Han Xue; Bo-fei Su; Yi-fan Chen; De-he Wang; Lei Shi; Kang Bai; Fei Hou; Jian-ku Hou; Hui-ling Bao; et al. (Poultry Science, 2024)
ABSTRACT: Follicular atresia in chickens reduces the number of follicles that can further develop, leading to decrease egg laying. Endoplasmic reticulum stress (ERS) can initiate a unique pathway inducing the apoptosis of follicular granulosa cells, thus reducing egg laying. Melatonin (MEL) is involved in the regulation of follicle development, ovulation, and oocyte maturation, and is closely related to follicle fate. Mammalian target of Rapamycin (mTOR) signaling pathway plays an important role in cell growth regulation, and that there is a possible crosstalk between melatonin and mTOR activity in granular cells maturation and ovulation. This study aimed to investigate whether MEL inhibits ERS and follicular granulosa cell apoptosis by regulating ATF4 to activate mTOR signaling pathway in chickens. Frist, we established an in vitro ERS cell model using tunicamycin (TM). The results showed that different concentrations of TM exhibited dose-dependent inhibition of cell activity and induction of granulosa cells (P<0.01). Therefore, we chose 5 µg/mL of TM and a treatment time for 6 h as the optimal concentration for the following experiments. Then we investigate whether melatonin can inhibit ERS. TM treatment decreased the cell viability and Bcl-2 expression, increasing ROS levels and the mRNA expression of Grp78, ATF4, CHOP, PERK, eIF-2α, and BAX (P<0.01), whereas TM+MEL treatment significantly inhibited these changes (P<0.01). Then we explored whether melatonin protects follicular granulosa cells from ERS-induced apoptosis through the mammalian target of rapamycin (mTOR) signaling pathway by regulating ATF4, we found that ATF4 knockdown inhibited ERS by decreasing the expression of ERS-related genes and proteins and activating mTOR signaling pathway by increasing the protein expression of p4E-BP1 and pT389-S6K (P<0.001), while these changes were promoted by TM+si-ATF4+MEL treatment (P<0.01). These results indicate that MEL could alleviate TM-induced ERS by regulating ATF4 to activate mTOR signaling pathway in follicular granulosa cells, thus providing a new perspective for prolonging the laying cycle in chickens.